Letter - Stolz, George
010-0089-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VIIe TELEGRAMS : INTERFED-PARIS TELEPHONE : INVALIDES 45-88 EXECUTIVE COMMITTEE: President: W. M. Citrine, Great Britain Vice-Presidents : H. Jacobsen, Denmark; L. Jouhaux, France; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels Letter Sit. Espagne No. 110 21st September 1936. Mr. H. V. Tewson, LONDON. Dear Comrade Tewson, Comrade Hicks rang up this afternoon and asked for information about Spain fot the meeting tomorrow. I am enclosing herewith the report I have made for our Bulletin, and should be glad if you would transmit it to him. As I mentioned to Comrade Hicks on the 'phone, the comrades of the Spanish National Centre are anxious to speak on the situation in Spain in public meetings in Paris, Brussels and London. These meetings could take place after the General Council meeting. I have proposed the evening of the 28th to our French comrades for the meeting here, and suggested the presence of a British comrade also. As Comrade Hicks will be on the spot for the General Council meeting in any case, this can easily be arranged. We are trying to fix a meeting in Brussels for a day or two later, so the meeting in London could be towards the end of the same week. You might possibly like arrangements to be made for a French comrade to speak at the same meeting. I should be glad to know as soon as possible if you are in agreement with the proposal and, if so, the date for which the meeting can be fixed. Yours sincerely, G. Stolz, Assistant Secretary: 292/946/10/97